Construction of the SDN Control Level Based on ONOS - Romanov, O.; Korniienko, N.; Обод, І. І.; Свид, І. В. (UkrMiCo, 2021)
Possibilities of construction of logically centralized control plane in SDN networks on the basis of open network operating system ONOS are considered. The structure of the controller and its main functional blocks are considered, which provide the collection of information about the state of network elements, the solution of the main control tasks, the interaction of control systems built on different technological bases. The role and place of open network operating system in the controller structure are shown, the description of ONOS multilevel architecture in the form of a set of functional modules is given, the purpose and functions of ONOS subsystems are analyzed, protocols and interfaces that allow to present SDN network as a model are described. The peculiarity of the model is that the managed network can be represented as a set of virtual network functions. Therefore, the control process becomes independent of which vendor's equipment was used to build the network, as well as whether the network is built on real physical elements or virtual ones.
Keywords: Open Network Operating System; ONOS; Controller; SDN; Control Plane SDN; Data Plane SDN